Influence of machining constraints on surface quality of ferrous and non-ferrous materials. (2021) - Bejaxhin, A. Bovas Herbert; Ramkumar, K.
Abstract: In the present scenario, surface quality achievements is a challengeable task among the product development sectors. Most of the influencing parameters can be interrupted to regulate the surface unevenness. Based on the previous literature survey, many researchers found many surface-oriented problems were raised due to the unplanned machining conditions. Here in our project work, the suitable machining conditions speed, feed, and depth of cut can be adopted from the previous literature reviews and its conclusions. This can be optimized and will give precise results of surface roughness which will be predicted through the milling simulation Deform 3D. The array formation in Minitab helps to conduct the experimental part in a very easy manner. We can easily identify the parameter that makes the roughness good or worse based on the load predictions and stresses.